SISTEM PENDUKUNG KEPUTUSAN PENENTUAN CALON PENERIMA BEASISWA PROGRAM INDONESIA PINTAR PADA SDN NEGERI 1 RANGKASBITUNG TIMUR DI RANGKASBITUNG DENGAN METODE MOORA - saroji; Riswal Hanafi Siregar (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The Smart Indonesia Scholarship Program is educational assistance organized by the government, in order to help ease the burden on underprivileged students so they can continue their education and to improve the quality of human resources through education. SDN 1 Rangkasbitung Timur consistently helps provide scholarships for this smart Indonesia program. To get the scholarship, it will help the school or officers in determining which students are entitled to get the PIP scholarship. To make it easier for schools and officials, it is necessary to have a decision support recommendation system that functions to assist in the selection of potential PIP scholarship recipients. In this study using the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method, by implementing a decision support system the school or officers can easily evaluate objectively, accurately and be accepted by students who are eligible to receive PIP scholarships. The final results obtained from this study were that A4 received the highest score, namely 0.238711784, and was selected as a student entitled to a Smart Indonesia Program scholarship.